Avaliação crítica e comparativa do gerenciamento de resíduos químicos em laboratórios de ensino e pesquisa de instituições de ensino superior (IES): estudo de caso do Campus Diadema da UNIFESP - Arantes, Marcus Vinicius Carvalho [UNIFESP] (2017)
Over the last decades, the challenge inherent to the need to implement an chemical waste environmentally management program has been raising environmental awareness in the different segments of the Brazilian and world academic community. The differents actors in these academic segments have come to recognize the potential social and environmental impacts that this type of waste can generate, especially when there is no correct chemical waste management program. In view of this worrying scenario, the Higher Education Institutions (HEI) have been seeking to adapt to this new reality, through the establishment of Chemical Waste Management Programs (CWMP) for chemical residues from their teaching and research laboratories. Bearing in mind, however, the normative dictates of environmental laws related to the subject, such as Resolutions of ANVISA RDC nº. 306/04 and CONAMA nº. 358/05, NBRs and other Technical Standards. The present study proposes to study the CWMP of the Chemical Institutes (CI) of the Cidade Universitária and ESALQ both campi of the University of São Paulo (USP) and the CI of the UNICAMP to subsequently point out possible improvements and adequations (propositions) to chemical waste management implemented at the Diadema campus UNIFESP. The methodology adopted in the present study is based on the transversal analysis between the CWMPs of the three IQs of the HEIs consolidated with the PGRQ implemented at the Diadema campus of UNIFESP. It was verified, through the transversal analysis, that from the experiences of chemical waste management adopted in each HEI evaluated, it was possible to delineate proposals for improvements to the Diadema campus, looking for adequate to the reality of this campus.